Kegiatan Literasi Kitab Akhlakul Lil Banin Untuk Meningkatkan Akhlakul Karimah Peserta Didik - Azizah, Siti Wardiyatul; Kafiul Khuluq, Muhammad Shahinshah; Santoso, Try Riduwan (THORIQOTUNA: Jurnal Pendidikan Islam, 2025)
This study aims to provide an overview of the implementation of literacy activities using the Akhlakul Lil Banin text to enhance the noble character (akhlakul karimah) of students at SMP Islam Serba Bakti Suryalaya. This research employs a descriptive qualitative method, with data gathered through observation, interviews, and documentation. This approach helps the researcher gain an in-depth understanding of the literacy program's implementation. Based on the findings, the Akhlakul Lil Banin literacy activities have proven effective in improving students' noble character. This is reflected in behavioral changes, with students displaying greater adherence to school rules, behaving well, and showing respect both at school, home, and in the community. The literacy program is conducted systematically, encompassing the stages of planning, execution, and evaluation. It involves several important stages: the habituation stage, the development stage, and the learning stage. The teaching methods applied include the bandongan method, lectures, question-and-answer sessions, and demonstrations. The materials taught cover ethics towards Allah SWT, fellow humans, and the environment. Additionally, this program helps students practice reading and writing in Arabic and develop critical thinking skills in evaluating the information they receive. Therefore, this literacy activity not only plays a role in religious education but also in shaping noble character in students, positively impacting their daily lives.